Experiences of nurses studying towards post-basic qualifications during COVID-19 in KwaZulu-Natal - Dudu G. Sokhela; Kathleen Nokes; Penelope M. Orton (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The COVID-19 pandemic caused abrupt closure of schools including higher education institutions. The transition from in-person to virtual teaching platforms caused challenges for frontline nurses in post-basic programmes. Nurses were forced to divide their efforts between responding to the pandemic and their studies.